Pelatihan Refleksi Pembelajaran yang Bervariasi pada SMP Negeri 9 Kupang - Saragih, Fernando; Nggandung, Yeheskial; Data, Ari; Loe, Andri P; abolladaka, Jacob; Lulan, Ninda Anaci (Jurnal Kelimutu Pengabdian Masyarakat, 2024)
This community service activity was conducted at SMP Negeri 9 Kupang to improve teachers' ability to implement varied learning reflections. Based on survey results, 50% of teachers mastered learning reflections well, 35% had sufficient mastery, and 15% were lacking. This issue arose due to the lack of intensive training and guidance on diverse reflection methods. The aim of this activity was to provide in-depth training to teachers, enabling them to apply learning reflections more effectively. The method used was participatory training, involving hands-on practice in applying various reflection techniques. The results indicated an improvement in teachers' ability to creatively use reflection methods, leading to better learning quality. In conclusion, this training successfully helped teachers master more varied reflections, contributing to enhanced student achievement through a higher-quality learning process.